2011
DOI: 10.3797/scipharm.1103-16
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel Pyrimido[4,5-d]pyrimidine CDK2 Inhibitors as Anti-tumor Agents

Abstract: A series of 2,5,7-trisubstituted pyrimido[4,5-d]pyrimidine cyclin-dependent kinase (CDK2) inhibitors is designed and synthesized. 6-Amino-2-thiouracil is reacted with an aldehyde and thiourea to prepare the pyrimido[4,5-d]-pyrimidines. Alkylation and amination of the latter ones give different amino derivatives. These compounds show potent and selective CDK inhibitory activities and inhibit in vitro cellular proliferation in cultured human tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Since then, most of the pyrimidopyrimidines are prepared by condensation reaction using substituted pyrimidine intermediates via a single or multistep process. Presently, the most frequently used methods to construct pyrimidopyrimidines mainly depend on the multi‐component reactions (MCRs) [59–62] or the cycloaddition reactions [63–67] involving 6‐aminouracil derivatives (Scheme 1). Pyrimidopyrimidines are also synthesized using a regiospecific one‐pot reaction under solvent‐free microwave irradiation conditions [59,63–65,68] .…”
Section: Synthesis Of Pyrimidopyrimidinesmentioning
confidence: 99%
“…Since then, most of the pyrimidopyrimidines are prepared by condensation reaction using substituted pyrimidine intermediates via a single or multistep process. Presently, the most frequently used methods to construct pyrimidopyrimidines mainly depend on the multi‐component reactions (MCRs) [59–62] or the cycloaddition reactions [63–67] involving 6‐aminouracil derivatives (Scheme 1). Pyrimidopyrimidines are also synthesized using a regiospecific one‐pot reaction under solvent‐free microwave irradiation conditions [59,63–65,68] .…”
Section: Synthesis Of Pyrimidopyrimidinesmentioning
confidence: 99%
“…As per the reported literatures, pyrimidine fused with different heterocycles such as furan, thiophene, pyrrole, pyrimidine, indole, pyrimidine, acridone, pyrazole, thiazole, and pyridine acts as EGFR inhibitors. Out of which pyrimidine combined with pyrazole ( Zhang et al, 2016 ; Jorda et al, 2019 ; Massaro et al, 2021 ), pyrrole ( Shi et al, 2021 ), pyrimidine ( El-Moghazy et al, 2011 ), and pyridine ( Barvian et al, 2000 ; Caballero et al, 2008 ; Abbas et al, 2019 ) shows inhibitory activity not only against EGFR but also against CDK. It is suggested that pyrimidine fused with the N- containing heterocyclic system acts as a dual inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidines are known as valuable heterocyclic compounds because their derivatives have been known to display a wide range of pharmacological and interesting biological activities such as antimicrobial, antiallergic, cardiotonics, antihypertensive, vasodilators and anticancer . These compounds could be synthesized using different catalysts including acetic acid, p‐toluenesulfonic acid, poly‐ethylene glycol‐bond sulfonic acid, and molecular iodine …”
Section: Introductionmentioning
confidence: 99%